P-113 Hospice Night Response Service – are we providing timely care in the community outside of normal working hours?. (19th November 2022) - Allkins, Rebecca; White, Sallyann
Abstract : Background: Access to timely palliative care is essential to provide safe care (Williams, Donaldson, Noble, et al., 2019. Palliat Med. 33:346; NHS. NHS Long term plan, 2019; NHS England. NHS operational planning and contracting guidance. [Internet], 2021 [cited 2022 Jan 14]). Outside of normal working hours, our Night Response Nursing Service visits patients known to the hospice with urgent palliative care needs and also District Nursing patients. A team of either 2 Nurses or a Nurse and Healthcare Assistant (HCA) visit patients within two districts covering an area of approximately 70.76km. Aim: An audit was performed to enable us to more accurately estimate time to arrival for patients and/or families and to ensure that the hospice is providing timely care out of normal working hours. Methods: From 1 November to 6 December 2021, times of incoming call(s) to the Night Response Team were documented along with the arrival time of the Nurse(s)/HCA. The area where the patient lived and their identification number were documented. Reasons for delays were analysed along with any differences in times between areas visited and hospice patients versus District Nurse patients. Results: The average response time was 1 hour 4 minutes, with little variation between the healthcare districts despite one district covering a larger geographical area. There was no difference between the time to arrival for hospice and District Nurse patients. 91% of visits had a time to arrival within 2 hours. Conclusion: Our average times to arrival are above the NHS national target of 70% of patients being reached by an urgent community response service within 2 hours. The audit has allowed the Night Response Team to give an evidence-based answer when patients and/or families ask for a real time estimate of nurse arrival time. A repeat audit will be undertaken which will include a patient/relative satisfaction survey. This will give some indication to the impact that wait times have on service users in the community. Little research can be found on this currently.